واقع أداء مديري مدارس التعليم الأساسي الحلقة الأولى من وجهة نظر المعلمين والمديرين وعلاقته ببعض المتغيرات دراسة ميدانية في مدينة اللاذقية - بركات, غسان; ناصر, رنا (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research aimed at recognize the reality of performance of the schools administrators of the basic teaching (level one) in the city of Lattakia at the light of the British total quality management standards (skills, adjectives), from the view of administrators and teachers according to the following variables: (the functional name, scientific and educational qualification, expertness, training courses). The researcher used the descriptive approach, and to achieve the purposes of research, the researcher designed questionnaire composed of (40) clause, it distributed on five axes, Skills (leadership, decision making, communication, self-management), and the behavioral Adjectives, and the research was applied on random classist sample composed of (64) teacher, and (6) administrators of schools of basic teaching in Lattakia city.Results have showed that the level of performance of the schools administrators has been at a middle high degree, and also showed that there are differences with statistical significance between the averages of the teachers answers, and the averages of the Schools Administrators answers, on fields of the questionnaire, according to the variables (the functional name, the expertness) in favor of the schools administrators, to the skills (the leadership, decision making, the communication), and for the expertness from (5) to (10) years. Whereas the results did not show statistical significance differences among sample answers averages, according to the variables of scientific and educational qualification, and the training courses. The researcher has presented suggestions for the improvement of the performance of the schools administrators. The most important are: an increase in the number of training courses for the schools administrators, and the continued training for administrators according to the standards of the total quality management.هدف هذا البحث إلى معرفة واقع أداء مديري مدارس التعليم الأساسي الحلقة الأولى في مدينة اللاذقية, في ضوء معايير إدارة الجودة الشاملة البريطانية (المهارات والصفات) من وجهة نظر المعلمين والمديرين, تبعاً للمتغيرات التالية (المسمى الوظيفي, المؤهل العلمي والتربوي, الخبرة, الدورات التدريبية), وذلك باستخدام المنهج الوصفي, ولتحقيق أهداف البحث صُممت استبانة مكونة من (40) بنداً, موزعة على خمسة محاور رئيسية هي: مهارات (القيادة, واتخاذ القرار, والاتصال, والإدارة الذاتية), والصفات السلوكية, وطُبّق البحث على عينة طبقية عشوائية مؤلفة من (64) معلماً ومعلمة, و(6) مديري مدرسة في مدينة اللاذقية, وبينت النتائج أن مستوى أداء مديري المدارس جاء بدرجة مرتفعة, كما بينت النتائج وجود فروق ذات دلالة إحصائية بين متوسط إجابات المديرين ومتوسط إجابات المعلمين على محاور الاستبانة بالنسبة إلى متغيريّ (المسمى الوظيفي, والخبرة), وذلك لصالح المديرين, بالنسبة إلى محاور مهارات (القيادة, اتخاذ القرار, الاتصال), ولذوي الخبرة ضمن فئة 5-10 سنوات, ولم تظهر النتائج فروق ذات دلالة إحصائية بين متوسط إجابات أفراد العينة تبعاً لمتغيري المؤهل العلمي والتربوي, والدورات التدريبية.وقدمت الباحثة مقترحات لتحسين أداء مديري المدارس وتطويره, أهمها زيادة عدد الدورات التدريبية للمديرين والتدريب المستمر للإداريين وفق معايير إدارة الجودة الشاملة.